A study on simulation analysis for laser-welded I-core sandwich plate with different material properties and T-joint weld characteristic - Saffirna, M.S.; Jiang, X.X.; M.R., M.Rejab; Lim, K.S; N.N., Guo; Wang, Bangle (Elsevier Ltd, 2022)
Stiffness and strength of sandwich plate vary depending on similar (SI) or dissimilar (DSI) material element (faceplate or core) and laser weld geometry. The issues of I-core sandwich plate characteristics are essential to attain practical sandwich plate application. Hence, research on different material properties and T-joint weld characteristics of I-core sandwich steel plate presents a positive understanding of various character factors that affect sandwich plate bending performance. In this paper, the I-core sandwich steel plate characteristic was investigated using finite element analysis (FEA). The 3-point bending with a fine meshing, interaction of elements, and load applied was kept constant. The partition size at the laser weld geometry is smaller, and the partition size continuously grows when further away from the weld geometry. The result shows that a combination of weak and strong material on either element will reduce I-core sandwich's stiffness and strength unless strong material is assigned at the faceplate and core. Moreover, there is a significant change when rootgap is present. This influencing the centric and eccentric of the weld. The weld width produces a perfect bending as wholesome T-joint, yet to achieve such traits is impossible in reality but possible when the weld length is closer to the length of the core. The exploration of these characteristics in response to I-core sandwich steel plate holds a good response in engaging for the multiple variables that affect the plate's stiffness and strength.